Bonus or bias? Mechanisms of sex specific wage compensation - Achatz, Juliane; Gartner, Hermann; Glück, Timea (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2005)
To what extent is the gender wage gap of fulltime employees due to differences in productivity-related characteristics, to discrimination of female employees, and how is the wage gap affected by firm specific features? To analyze these problems we use a linked employer-employee database in 2000, made available by the German Institute for Labour Market Research. In particular, we address the effect on wage levels of the sex composition of occupations within firms (job cells). Our estimations rely on the decomposition of the wage differential proposed by Oaxaca and Blinder. We find that only one third of the gender gap in wages is explained by human capital differences between men and women. With increasing proportions of women within job cells we observe decreasing wage levels for men and women but with higher rates of decline for women than for men. While works councils are shown to have a positive impact on wage levels, women are found to profit most from their presence within firms.
Keywords: gender wage gap; occupational sex segregation; discrimination